Judaism's other geographies: Franz Rosenzweig and the state of exile. (June 2016) - Dubow, Jessica
Franz Rosenzweig (1886–1929), the German-Jewish theologian and philosopher, presents us with what can be called a 'politics of Judaic theology'. Focussing on the particularities of Judaic time and space in his major work, The Star of Redemption (1921), this article argues for the importance of revisiting Rosenzweig to recuperate a history of thought opposed to the entailments of secular time with sovereign territory. Essaying between Rosenzweig's early 20th-century theology and the political present, I then bring him into dialogue with the voices of Judith Butler and Jaqueline Rose who, from the varying perspectives of ethics and psychoanalysis, insist on an originary displacement at the heart of Jewish identity and, with this, the impossibility of any project of national affirmation. Indeed, when read together with contemporary challenges to political Zionism, I suggest that Rosenzweig's theological understandings of space and time offer an alternative – and anterior – perspective from which to critique the ambitions of the Jewish nation-state.